2010
DOI: 10.1029/2009jb006817
|View full text |Cite
|
Sign up to set email alerts
|

Bidirectional and unidirectional fracture growth during hydrofracturing: Role of driving stress gradients

Abstract: [1] An unexpected observation from induced seismicity during stimulation experiments was the identification of asymmetric bidirectional and unidirectional growth of the seismic front and back front, indicating asymmetric growth of the hydrofracture itself. We develop and analyze a new analytical hydrofracture model that considers for the first time the effect of stress and pore pressure gradients on growth. It is based on plane strain linear elastic fracture mechanics and further considers 1-D laminar flow, th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
51
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(58 citation statements)
references
References 43 publications
(47 reference statements)
7
51
0
Order By: Relevance
“…The initial vertical propagation of the dyke involves some seismicity in an otherwise aseismic region (as noted for other intrusions, e.g. Belachew et al 2011), and the seismicity in this region during the May 2010 dyke intrusion is (1) only during the initial injection, and (2) only tracking the vertical motion at the very centre, which is consistent with the seismicity tracking the propagation of the tip during the initial stages of dyke propagation Dahm et al 2010;Belachew et al 2011). Seismicity propagates north and south from the segment centre, emplacing two dyke segments of approximately 8 and 10 km length, which show differing final geometries and variations in seismicity.…”
Section: Sequence Of Eventssupporting
confidence: 63%
“…The initial vertical propagation of the dyke involves some seismicity in an otherwise aseismic region (as noted for other intrusions, e.g. Belachew et al 2011), and the seismicity in this region during the May 2010 dyke intrusion is (1) only during the initial injection, and (2) only tracking the vertical motion at the very centre, which is consistent with the seismicity tracking the propagation of the tip during the initial stages of dyke propagation Dahm et al 2010;Belachew et al 2011). Seismicity propagates north and south from the segment centre, emplacing two dyke segments of approximately 8 and 10 km length, which show differing final geometries and variations in seismicity.…”
Section: Sequence Of Eventssupporting
confidence: 63%
“…We also observe unidirectional rather than bidirectional growth. Thus, we argue that the mechanism proposed by Dahm et al (2010) might not be sufficient to explain asymmetric fracture growth in our case. To date, it is not entirely clear why fractures grew in such a unidirectional manner.…”
Section: Comparison To Overcoring Stress Measurementsmentioning
confidence: 45%
“…Dahm et al (2010) suggested that asymmetric bidirectional fracture growth during injection and bidirectional to unidirectional growth after shut-in may be driven by gradients of in situ stress or pore pressure. In our case, fractures grow upwards in the case of HF1 and HF2 and downwards in the case of HF3, which would imply that a presumed stress or pressure gradient would change direction between 13 and 8 m borehole depths.…”
Section: Comparison To Overcoring Stress Measurementsmentioning
confidence: 99%
“…The term "overpressure" in the sense used here is well-established in the technical literature (Heimpel and Olson, 1994;Bonafede and Rivalta, 1999a,b). However, p o is also referred to as driving pressure or driving stress (Pollard and Segall, 1987;Vermilye and Scholz, 1995;Dahm et al, 2010), or as net pressure (Valko and Economides, 1995). Fluid overpressure, as defined here, is not to be confused with an abnormal pore formation pressure.…”
Section: Fluid Overpressure Of Hydrofracturesmentioning
confidence: 99%